Short Communication: First record of Hirschmanniella mucronata (Nematoda: Pratylenchidae) in Yogyakarta, Indonesia - Siwi Indarti; Alan Soffan; MUHAMMAD MAULANA FARDANI ANDRASMARA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Indarti S, Soffan A, Andrasmara MMF. 2020. Short Communication: First record of Hirschmanniella mucronata (Nematoda: Pratylenchidae) in Yogyakarta, Indonesia. Biodiversitas 21: 2068-2073. Hirschmanniella spp. is one of the worldwide plant-parasitic nematodes affecting major losses in rice production and impact up to 25% yield losses especially on irrigated rice. Infection of Hirschmanniella spp. on the root system leading to the typical symptom of red color in the rice rooting system. In order to identify the species variation of Hirschmanniella spp. from the collected samples in Yogyakarta Province of Indonesia, a molecular-based identification using Polymerase Chain Reaction (PCR) method was conducted, complemented by morphological identification technique. PCR based identification was carried out by amplifying the area of ??28S rRNA using universal nematode primer (D2A / D3B) which resulting about 766 bp of amplicon. Blastx analysis from Genbank showed that Cangkringan sample confirmed to be H. mucronata species, while other samples from Banguntapan and Imogiri were H. oryzae species. The Cangkringan samples of H. mucronata have 97.5 % similarities with Belgium sample, forming separate clades with other samples. While both Banguntapan and Imogiri samples have the 99 % similarity with H. oryzae and were located in the same clade, but separated from Cangkringan sample. Morphological identification confirmed both species were distinctly based on the unique characters of the tail tips. H. mucronata therefor is the first report nematode species in Indonesian rice field. Precaution should be designed to prevent the potential distribution of H. mucronata to other areas.